Smartwatches and measurement of physical activity, sedentary behavior, and sleep: a scoping review - José Francisco da Silva; Antonio Henrique Germano-Soares; Luis Carlos Barbosa Silva; Valter Cordeiro Barbosa Filho; Tuillamys Virgínio de Oliveira; Thiago Coelho de Aguiar Silva; Rafael Miranda Tassitano (Revista Brasileira de Atividade Física e Saúde)
Introduction: The use of accelerometers to measure physical activity (PA), sedentary behavior (SB), and sleep has significantly impacted public health, though limitations such as storage capacity and cost persist. Smartwatches have emerged as promising alternatives, providing objective measurements and real-time data extraction. Despite their growing popularity, there is still a lack of comprehensive information on smartwatch models, sensors, and data transfer methods. Objective: To map the technical characteristics related to sensors, metrics and type of data transfer of different models of smartwatches capable of measuring PA, SB and sleep. Methods: The review utilized the Joanna Briggs Institute guidelines and included 143 smartwatch models from 12 manufacturers. Results: All models measured PA, step counts, and daily calories, while the SB metric was present in 35.5% of the smartwatches, sleep duration in 93.1%, and 35.5% of smartwatches measured PA, SB and sleep simultaneously. The most common smartwatches sensors were photoplethysmography, geolocation and gyroscope. All models were found to have Bluetooth connectivity, with 55% of the models featuring Wi-Fi connectivity, and only 11.3% of smartwatches having a mobile network. Conclusion: This scoping review can guide studies, interventions, and healthcare professionals, as well as assist end-users to select an appropriate smartwatch for measure PA, SB, and sleep. Scoping review registration: https://osf.io/3s9x5